Synthesis of a novel collector based on selective nitrogen coordination for improved separation of galena and sphalerite against pyrite. (23rd November 2020) - Zhang, Wanjia; Feng, Zhitao; Mulenga, Happy; Sun, Wei; Cao, Jian; Gao, Zhiyong
Graphical abstract: Highlights: CSC-1 collector was synthesized and used in flotation of Pb/Zn sulfide minerals. CSC-1 held better flotation selectivity to Pb/Zn versus Fe sulfides than xanthate. CSC-1 has a stronger affinity towards Pb 2+ and Zn 2+ than Fe 2+ . CSC-1′s higher selectivity is caused by the introduced N chelation atom. Abstract: During the separation of sulfide minerals, the problem of low selectivity always arises. A novel thiadiazole derivative (CSC-1) was developed for the flotation of sulfide minerals. The results of flotation tests showed that, compared with the conventionally-used ethyl xanthate, using CSC-1 as the collector, higher flotation recoveries of sphalerite and galena with improved selectivity against pyrite were obtained. Furthermore, zeta potential measurement and FTIR-spectra analysis results revealed that CSC-1 preferred to adsorb onto sphalerite and galena, rather than onto pyrite. The interaction mechanisms of CSC-1 with sphalerite and galena are electrostatic forces and chelation by forming N–Pb–S / N–Zn–S coordination bonds. DFT calculations demonstrated that both the Gibbs free energy difference (ΔG) and the distortion energy difference (ΔD) of metal ion–CSC-1 configuration before and after coordination follow the order: Pb 2+ –CSC-1 < Zn 2+ –CSC-1 < Fe 2+ –CSC-1, which further confirmed CSC-1 has preferable chelating selectivity towards Pb 2+ and Zn 2+, rather than Fe 2+ . This study indicates that CSC-1 has great potential for industrial application in sulfide mineral flotation.